2017
DOI: 10.1109/tnsre.2017.2698005
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Assessment of a Rollator-User’s Condition During Rehabilitation Using the i-Walker Platform

Abstract: Patient condition during rehabilitation has been traditionally assessed using clinical scales. These scales typically require the patient and/or the clinician to rate a number of condition-related items to obtain a final score. This is a time-consuming task, specially if a large number of patients are involved. Furthermore, during rehabilitation, user condition is expected to change steadily in time, so assessment may require to run these scales several times to each user. To save time, much effort has been fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 33 publications
0
21
0
1
Order By: Relevance
“…This is used to determine the swaying phase of the gait cycle when the angular velocity has zero-value. A previous methodology using the i-Walker was proposed in [2] using the pushing force inputs to identify gait cycles. The study was applied to a group of geriatric users with different ambulatory problems, including individuals with leg amputations.…”
Section: Methodsmentioning
confidence: 99%
“…This is used to determine the swaying phase of the gait cycle when the angular velocity has zero-value. A previous methodology using the i-Walker was proposed in [2] using the pushing force inputs to identify gait cycles. The study was applied to a group of geriatric users with different ambulatory problems, including individuals with leg amputations.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that an instrumented wheeled walker can also be used to reflect changes in gait during rehabilitation and predict the outcomes of clinical assessments [21]. Presented results revealed the ability of an instrumented walker to predict Tinetti assessment scores (measure of balance and gait function) on the fly.…”
Section: Introductionmentioning
confidence: 90%
“…The second method, recently developed, implies the use of wearable sensors with a longterm monitoring system. The equipment included is light, small, inexpensive, and can easily be carried for long periods and distances to quantify gait parameters [13][14][15]. Seven studies were included in this section with 321 participants involved (see Table 1) [16][17][18][19][20][21][22].…”
Section: Gait and Posture Difficultiesmentioning
confidence: 99%